Pasti liberalnega feminizma v polju literarnega - Burcar, Lilijana (Vzgoja in izobraževanje, 2019)
The article sheds light on the basic fallacies and shortcomings of liberal feminism, a strand of Western feminism that has been unquestioningly adopted as part of official governmental policies following the destruction of socialism and the ousting of systemic feminism. Unlike systemic feminism, liberal feminism does not rest on the investigation of structural causes of women's systemic marginalization and their othering in capitalist patriarchies. With its narrow and biologically essentialist emphasis on women's quotas, liberal feminism avoids this issue, thus helping to maintain the status quo in capitalist patriarchies. It does so by merely advocating in favour of (a handful of) more women occupying the so-called positions of power, primarily in managerial and political top job positions. This it offers as a litmus test of women's progress and empowerment in general despite the fact that the majority of women are facing a major downsizing and shrinking of the public sector services such as childcare and elderly care provision. As amply proven by systemic feminism in theory and practice, it is the wide availability and accessibility of the latter that functions as a precondition for women's independence and advancement, both in the public and the private sector. In the literary field, the adoption of liberal feminism along with all its deficiencies and failings can be clearly seen in the popular textual approach that rests on the mere counting of the number of girl characters appearing in a text and on the ratio between the boy and girl protagonists. This de-substantiated approach does not help to cultivate the much needed critical consciousness on the part of teachers nor does it contribute to the social and contextualized gender awareness on the part of the young readers. The end result of such critical non-engagement with literary texts is the same one as reflected in and promoted by official policies in capitalist patriarchies on a state level. The point is to scratch the surface only, that is, to talk about gender without addressing the actual structural issues and therefore to keep capitalist patriarchies intact with a few concessions granted to upper-class women.
Keywords: liberalni feminizem; literarne študije; mladinska književnost; sistemski feminizem